Interplay between Narrative and Bodily Self in Access to Consciousness: No Difference between Self- and Non-self Attributes - Noel, Jean-Paul; Blanke, Olaf; Serino, Andrea; Salomon, Roy (Frontiers in Psychology, 2017)
The construct of the ‘self’ is conceived as being fundamental in promoting survival. As such, extensive studies have documented preferential processing of self-relevant stimuli. For example, attributes that relate to the self are better encoded and retrieved, and are more readily consciously perceived. The preferential processing of self-relevant information, however, appears to be especially true for physical (e.g., faces), as opposed to psychological (e.g., traits), conceptions of the self. Here, we test whether semantic attributes that participants judge as self-relevant are further processed unconsciously than attributes that were not judged as self-relevant. In Experiment 1 a Continuous Flash Suppression (CFS) paradigm was employed with “self” and “non-self” attribute words being presented subliminally, and we asked participants to categorize unseen words as either self-related or not. In a second experiment, we attempted to boost putative preferential self-processing by relation to its physical conception, that is one’s own body. To this aim, we repeated Experiment 1 while administrating acoustic stimuli either close or far from the body, i.e., within or outside peripersonal space. Results of both Experiment 1 and 2 demonstrate no difference in breaking suppression for self and non-self words. Additionally, we found that while participants were able to process the physical location of the unseen words (above or below fixation) they were not able to categorize these as self-relevant or not. Finally, results showed that sounds presented in the extra-personal space elicited a more stringent response criterion for “self” in the process of categorizing unseen visual stimuli. This shift in criterion as a consequence of sound location was restricted to the self, as no such effect was observed in the categorization of attributes occurring above or below fixation. Overall, our findings seem to indicate that subliminally presented stimuli are not semantically processed, at least inasmuch as to be categorized as self-relevant or not. However, we do demonstrate that the distance at which acoustic stimuli are presented may alter the balance between self- and non-self biases.